Características clínicas de crianças com paralisia cerebral em um serviço de referência - Carmo, Giovana Bezerra do (2006)
This research aimed to study the clinical conditions of children with cerebral palsy in a reference service in pediatric care in Fortaleza as well as identify the main risk factors for cerebral palsy, to determine its impact and the degree of impairment in normal development the study population, establish the average time elapsed between the perception of changes in the family development, diagnosis and medical referral and admission of the child in the service. This is a cross sectional study, conducted at the Center for Integrated Medical Care (NAMI), University of Fortaleza (UNIFOR) in the period from February to June 2005, evaluating 85 children with definite diagnosis of cerebral palsy (CP) in aged zero to twelve years, with changes in sensory-motor tone, posture and movement, visual and hearing deficits. The collected data were stored on base Electronic EPI-INFO version 6.01 and the following results: the sample comprised 50.6% of male children, with a mean age of 4 years and 3 months, 85.9% were coming from Fortaleza mean age at CP diagnosis of 11 months. There was a large percentage of children who suffered neonatal complications (77.4%) and respiratory distress leading to making 65.3% received care in the NICU. Most of the children had spastic CP (69.1%), severe (51.8%), quadriplegia (71.4%), only 27% communicated verbally and 53% were attending school regularly. It can be concluded that most children had severe sensory-motor and the first signs of such involvement were perceived by their families, although the majority have received pediatric care routine in the first year of life, few have been evaluated and received some guidance on the psychomotor development during the consultations, a fact that makes us aware of the need to make awareness among the primary care team about the importance of regular assessment of developments in the first year of life, so that we can to identify and refer children with potential delays and serious illnesses such as PC-time increasingly skilled, increasing the likelihood of a better quality of life.